On the paradox of prudential regulations in the globalized economy; International reserves and the crisis: a reassessment - Joshua Aizenman (University of California, Economics Department, 2009)
This paper discusses two pertinent policy issues dealing with the global liquidity crisis - global prudential regulation reform, and reassessment of using international reserves in the crisis. We point out the paradox of prudential regulations - while the identity of economic actors that benefited directly from crises avoidance is unknown, the cost and the cumbrance of regulations are transparent. Hence, crises that had been avoided are imperceptible and are underrepresented in the political discourse, and the demand for prudential regulations declines during prolonged good times, thereby increasing the ultimate cost of eventual crises. While the seeds of the present crisis were mostly home grown, international flows of capital magnified its costs. Global financial integration produces the by-product of regulatory arbitrage - capital tends to flow to underregulated countries, frequently resulting in excessive risk taking, in anticipation of future bailout. Dealing with regulatory arbitrage requires coordinated prudential regulations that should apply as equally as possible to domestic and foreign players. A coordinated globalized prudential regulation, by increasing the cost of prudential deregulation, would mitigate the temptation to under-regulate during prolonged good-times, thus adding a side benefit. We also analyze the different approaches to the use of reserves during the crisis and what this means for the global financial system. The deleveraging trigged by the crisis implies that countries that hoarded reserves have been reaping the benefits. The crisis illustrates the importance of the self insurance provided by reserves, as well as the usefulness of policies that channel a share of the windfall gains associated with improvements in the terms-of-trade to reserves and sovereign wealth funds. The reluctance of many developing countries to draw down on their reserve holdings raises the possibility that they may now suffer less from the fear of floating than from a fear of losing international reserves, which may signal deterioration in the credit worthiness of a country. While the selective swap lines offered by the FED to several EMs help, it falls short of dealing with the fear of losing reserves. Mitigating this concern should be the prime responsibility of the international financial institutions.
Keywords: F15; F33; F36; F55; 330; global prudential regulation; regulatory arbitrage; fear of losing international reserves; swap lines; Theorie der Regulierung; Währungsreserven; Finanzmarktkrise; Globalisierung; Welt